Importance of orthodontic intervention of the Class III malocclusion in mixed dentition - Dennyson Brito Holder da Silva; Ariane Salgado Gonzaga (Dental Press Editora, 2020)
ABSTRACT Introduction: Supervising the development of occlusion, managing problems during the transition from mixed to permanent dentition, as well as controlling environmental factors that contribute to establishing malocclusion, are important actions to achieve a Class I occlusion with facial balance. Among these problems, the malocclusions associated with dysfunctions such as mouth breathing or obstructive sleep apnea syndrome (OSAS), atypical swallowing and abnormal tongue position, open bites, crossbites and maxillomandibular discrepancies, and especially the Class III malocclusion can be listed. Objective: The purpose of this article is to present and discuss the main aspects relevant to the benefits of performing the treatment of Class III malocclusion in patients with growth.